Impact of access cavities on root canal preparation, restorative protocol quality, and fracture resistance of teeth - Heitor Silva PRADO; Igor Bassi Ferreira PETEAN; Natália Junqueira Saud FRANCO; Rafael Verardino CAMARGO; Kleber Kildare Teodoro de CARVALHO; Jardel Francisco MAZZI-CHAVES; Fabiane Carneiro LOPES-OLHÊ; Yara Teresinha Corrêa SILVA-SOUSA; Aline Evangelista SOUZA-GABRIEL; Manoel Damião SOUSA-NETO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The survival of endodontically treated teeth depends on the remaining tooth structure. The aim of this study was to evaluate the impact of different access cavities on root canal preparation, restorative protocol, and fracture resistance of endodontically treated teeth. Fifty-six mandibular molars were divided into control (n=8) and experimental (n=16) groups according to access cavity: Traditional, Conservative, and Truss; and redistributed (n=8) according to instrumentation protocols: Reciproc Blue and R-motion. After, teeth were scanned in micro-CT and then filled and redistributed according to composite resin restoration (n=8): Filtek One BulkFill and Filtek Z350. A new micro-CT scan was performed to analyze the restorative material. Then, samples were submitted to fracture resistance testing and the failure pattern was determined. Data were analyzed using paired T-test, ANOVA, Tukey, and chi-square tests (α=0.05). In Truss, R-Motion promoted less transportation in different thirds of root canals. Higher percentages of voids (5.05%) and filling material (11.7%) were observed in Truss. Fracture resistance values were higher for the control group, followed by Truss, Conservative, and Traditional. The predominant failure pattern was type-II. In Truss, reciprocating instruments with smaller taper showed less canal transportation. Also, Truss provided higher values of fracture resistance, although it presented a higher percentage of voids and remaining filling material. Thus, in Truss, reciprocating files with smaller taper showed less canal transportation, and these cavities provided higher values of fracture resistance, although it presented a higher percentage of voids and remaining filling material.